Site conditions shaped the effect of silvicultural management on the biodiversity of ectomycorrhizal fungi in mixed Nothofagus forests - Floriani, Franco Daniel; El Mujtar, Veronica Andrea; Mateo, Camila; Sola, Georgina Giselle; González Peñalba, Marcelo; Sbrancia, Renato; Marchelli, Paula; Fernandez, Natalia Veronica (Elsevier, 2024)
Ectomycorrhizas (EcM) constitute a crucial component of soil biota in forest ecosystems, where they perform functions of great ecological significance. Although there is available information about the individual effects of various factors shaping EcM fungal communities, it is still challenging to understand the intricate interaction among different environmental factors and forest management on these communities. Our aim was to evaluate the potential modulation of silvicultural management impacts by site conditions on different facets of EcM fungal biodiversity in mixed Nothofagus forests in northern Patagonia. We compared managed and unmanaged plots located in mesic and humid sites, and assessed root colonization by EcM, taxonomic α- and β- EcM fungal diversity, as well as relative abundance of functional EcM groups defined by fungal soil nutrient foraging strategies (exploration types). We found that the effect of silvicultural management on root colonization was not modulated by site conditions, being colonization percentages higher in the mesic site and in unmanaged plots. Conversely, the effect of silvicultural management on taxonomic α- and β-diversity of EcM fungi, as well as on the relative abundance of exploration types, was modulated by site conditions. We found that in the mesic site silvicultural management tended to increase the α-diversity of EcM fungal communities and changed the relative abundance of different EcM fungal taxa and EcM functional groups. In the humid site, silvicultural management did not generate changes in α-diversity, but a shift in the relative abundance of certain EcM fungal taxa and of different EcM functional groups was detected. These changes in taxonomic and functional EcM groups could be related to the intrinsic traits of the EcM fungal species present in each site (e.g., stress tolerance, water, and nutrient acquisition strategies) and how they interact with environmental disturbances, such as silvicultural management. Overall, the composition of EcM fungi in all groups was affected by the interaction of both factors, although the detected changes were mostly explained by modifications in the relative abundance of EcM fungi within each group rather than species replacement terms. Our study highlights the complexity of ectomycorrhizas dynamics in ecosystems and emphasizes the importance of considering belowground communities when analyzing the impacts of silvicultural management. Furthermore, our results also reveal that silvicultural management assessment and implementation should consider the environmental variation of the forest landscape.